Socioeconomic variation in the incidence of childhood coeliac disease in the UK - Zingone, Fabiana; West, Joe; Crooks, Colin J.; Fleming, Kate M.; Card, Timothy R.; Ciacci,, Carolina; Tata, Laila J. (BMJ Publishing Group, 2015)
BACKGROUND: Serological studies indicate that evidence of coeliac disease (CD) exists in about 1% of all children, but we lack estimates of current diagnostic patterns among children and how they vary by socioeconomic group.